Cities and villages in the religious conflict circle: Socio-demographic factors of communal and sectarian conflict in West Java, Indonesia - Jamaludin, Adon N. (HTS teologiese studies, 2021)
This article analyses the forms of religious conflict in cities (urban areas) and villages (rural areas) in Indonesia. The main locus of this study is in 11 regencies and cities in West Java, a province with the highest ranking of violations of religious freedom in Indonesia for the last two decades (2000–2020). These regencies and cities include: Bekasi Regency, Bekasi City, Bogor Regency, Bogor City, Tasikmalaya Regency, Bandung Regency, Bandung City, Kuningan Regency, Garut Regency, Cianjur Regency and Cimahi City. The study confirms that the sociological characteristics of urban and rural areas influence the tendency of different forms of conflict in both areas. On the one hand, heterogeneous urban social conditions tend to have an impact on the forms of conflict between religious communities – Muslims and Christians. On the other hand, the homogeneous rural social conditions affect the forms of conflict that are internal to religious communities or fellow Muslims. This study shows that religious conflict in a region cannot be generalised because each region has different socio-demographic conditions. Therefore, knowledge of differences in socio-demographic conditions in each region is very important because it will determine the form, causes and the ways to handle the conflicts in each region.Contribution: This study contributes to mapping the different sociological characteristics of religious conflict in cities and villages in West Java. It can be used as an illustration for other regions in Indonesia and Southeast Asia.